Characterization of mutations in patients with multiple endocrine neoplasia type 1. - Bassett, J; Forbes, SA; Pannett, A; Lloyd, SE; Christie, P; Wooding, C; Harding, B; Besser, G; Edwards, C; Monson, J; Sampson, J; Wass, J; et al. (1998)
Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant disorder characterized by tumors of the parathyroids, pancreatic islets, and anterior pituitary. The MEN1 gene, on chromosome 11q13, has recently been cloned, and mutations have been identified. We have characterized such MEN1 mutations, assessed the reliability of SSCP analysis for the detection of these mutations, and estimated the age-related penetrance for MEN1. Sixty-three unrelated MEN1 kindreds (195 affected and 396 unaffected members) were investigated for mutations in the 2,790-bp coding region and splice sites, by SSCP and DNA sequence analysis. We identified 47 mutations (12 nonsense mutations, 21 deletions, 7 insertions, 1 donor splice-site mutation, and 6 missense mutations), that were scattered throughout the coding region, together with six polymorphisms that had heterozygosity frequencies of 2%-44%. More than 10% of the mutations arose de novo, and four mutation hot spots accounted for >25% of the mutations. SSCP was found to be a sensitive and specific mutational screening method that detected >85% of the mutations. Two hundred and one MEN1 mutant-gene carriers (155 affected and 46 unaffected) were identified, and these helped to define the age-related penetrance of MEN1 as 7%, 52%, 87%, 98%, 99%, and 100% at 10, 20, 30, 40, 50, and 60 years of age, respectively. These results provide the basis for a molecular-genetic screening approach that will supplement the clinical evaluation and genetic counseling of members of MEN1 families.